Prevalence and molecular characterization of G6PD deficiency in two Plasmodium vivax endemic areas in Venezuela: predominance of the African A-202A/376G variant. (December 2016) - Vizzi, Esmeralda; Bastidas, Gilberto; Hidalgo, Mariana; Colman, Laura; Pérez, Hilda
Abstract Background Glucose-6-phosphate dehydrogenase (G6PD) deficiency causes acute haemolytic anaemia triggered by oxidative drugs such as primaquine (PQ), used forPlasmodium vivax malaria radical cure. However, in many endemic areas of vivax malaria, patients are treated with PQ without any evaluation of their G6PD status. Methods G6PD deficiency and its genetic heterogeneity were evaluated in northeastern and southeastern areas from Venezuela, Cajigal (Sucre state) and Sifontes (Bolívar state) municipalities, respectively. Blood samples from 664 randomly recruited unrelated individuals were screened for G6PD activity by a quantitative method. Mutation analysis for exons 4–8 ofG6PD gen was performed on DNA isolated from G6PD-deficient (G6PDd) subjects through PCR–RFLP and direct DNA sequencing. Results Quantitative biochemical characterization revealed that overall 24 (3.6 %) subjects were G6PDd (average G6PD enzyme activity 4.5 ± 1.2 U/g Hb, moderately deficient, class III ), while DNA analysis showed one or two mutated alleles in 19 of them (79.2 %). TheG6PD A-202A/376G variant was the only detected in 17 (70.8 %) individuals, 13 of them hemizygous males and four heterozygous females. Two males carried only the 376A → G mutation. No other mutation was found in the analysed exons. Conclusions The G6PDd prevalence was as low as that one shown by nearby countries. This study contributes to the knowledge of the genetic background of Venezuelan population, especially of those living in malaria-endemic areas. Despite the high degree of genetic mixing described for Venezuelan population, a net predominance of the mild AfricanG6PD A-202A/376G variant was observed among G6PDd subjects, suggesting a significant flow ofG6PD genes from Africa to Americas, almost certainly introduced through African and/or Spanish immigrants during and after the colonization. The data suggest that 1:27 individuals of the studied population could be G6PDd and therefore at risk of haemolysis under precipitating factors. Information about PQ effect on G6PDd individuals carrying mild variant is limited, but since the regimen of 45 mg weekly dose for prevention of malaria relapse does not seem to be causing clinically significant haemolysis in people having theG6PD A-variant, a reasoned weighing of risk–benefit for its use in Venezuela should be done, when implementing public health strategies of control and elimination.